Partial preservation of the normal thyroid gland based on tumor diameter may be possible in small medullary thyroid carcinoma: a two-center 15-year retrospective study - Fu, Guiming; Li, Xiaoyi; Guo, Fengli; Ruan, Xianhui; Zhang, Wei; Zhang, Weijing; Zhang, Yaping; Chen, Yibo; Li, Chunhua; Chen, Jin; Zheng, Xiangqian; Wang, Zhaohui; et al. (Frontiers in Oncology, 2023)
Background: At present, there are some controversies in the formulation of surgical protocol for small medullary thyroid carcinoma(s-MTC). We wanted to explore the feasibility of normal thyroid gland retention in small medullary thyroid carcinoma based on different tumor diameters and its prognostic impact on the tumor.The data of patients with stage T1 MTC treated at Tianjin Cancer Hospital and Sichuan Cancer Hospital from 2006 to 2021 were analyzed. The tumor diameters of 0.5 cm and 1.0 cm were used as dividing points. The outcomes were tumor recurrence, metastasis, or patient death. Survival was estimated by the Kapan-Meier curve.Results: A total of 121 T1 s-MTC patients were included, including 55 with total thyroidectomy (TT) and 66 with subthyroidectomy (Sub-TT). There were eleven cases of tumor recurrence and metastasis, and four patients died. When the tumor diameter was 1.0 cm as the cut-off point, tumor diameter (p = 0.010), TT (p = 0.028), unilateral and bilateral type (p = 0.009), and TNM staging (p = 0.007) had significant effects on progression-free survival (PFS). The tumor diameter, unilateral and bilateral type, and TT were risk factors for the prognosis of T1 MTC (p < 0.05).The tumor diameter of 1.0 cm can be used as a cut-off point for stage T1 MTC. Although there was no significant difference in overall survival (OS) between T1a and T1b in patients, tumor diameter significantly influenced PFS. TT is not necessary for patients with sporadic MTC with T1a.